Analysis of reciprocating O‐ring seal in the pressure‐balanced oil‐filled wet‐mate electrical connectors for underwater applications. (22nd August 2019) - Han, Quan; Chen, Haiyang; Yang, Wencong; Zhang, Yan; Yang, Juekuan; Chen, Yunfei
Abstract: The rapidly growing demand for wet‐mate electrical connectors in underwater projects has attracted the attention of researchers in the field. Sealing is the key to underwater connectors. In this paper, the reciprocating O‐ring seal during underwater operations of the pressure‐balanced connectors was studied. A numerical model containing the Reynolds equation, hyperelastic deformation, and asperity contact was used to describe mixed elastohydrodynamic lubrication (EHL) in the O‐ring seal. Results indicate that the friction force of the seal in the connector decreases directly with the increased sealed pressure, and its friction force is smaller than that in the conventionally hydraulic structure. As the sealed pressure increases, the minimum film thickness in the connector increases, which means a better lubrication in the deeper sea. The oil leakage in the connector increases with the sealed pressure, but the increase rate is smaller than that in the hydraulic structure. It proves that the design of pressure‐balanced structure can not only achieve wet‐mate operation at any depth but also facilitate its dynamic sealing performance.